The Law of Prioritizes Alms Over Qurban Worship During The Covid-19 Pandemic - Nadzira Luftiari; Aji Rystiawan; Siti Nurjanah; Fuhaida, Ulya (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
The purpose of this research is to find out about the law regarding prioritizing alms rather than sacrificial worship during the Covid-19 pandemic. This study uses the systematic literature review method which is a way of identifying, evaluating, and interpreting the availability of research that is relevant to the formulation of the problem under study. This study also uses a scientific methodological approach to summarize research results by regularly searching articles whose research focus is in the form of legal concepts of fiqh. Data analysis was conducted descriptively-qualitatively, with the following steps: Data Reduction: Grouping data relevant to the research, such as fiqh principles, views of scholars, and implementation in the field. Data Display: Organizing data into a thematic framework, such as sharia arguments, fatwas of scholars, and implementation in society during the pandemic. The results obtained from this study indicate that during the pandemic it created economic problems, which then gave priority to Muslims who were able to sacrifice to give alms in the form of money because this was in accordance with the recommendations of the Muhammadiyah fatwa.